The relation of BCG vaccination and severe malnutrition with the occurrence of tuberculous meningitis - Nofareni Nofareni; Bistok Saing; Ridwan M. Daulay; Bidasari Lubis (Paediatrica Indonesiana, 2004)
Objectives To assess BCG vaccination and nutritional states inchildren with tuberculous meningitis and their relations with theoccurrence of tuberculous meningitis.Methods A case-control study was conducted at the Divisionof Neurology, Department of Child Health, Adam Malik Hospi-tal, Medan, from January 1997 to December 2000. Subjects ofthis study were all tuberculous meningitis patients and primarytuberculosis patients as the control group. Odds ratio (OR) wasused to assess the risk of tuberculous meningitis in patientswith positive BCG vaccination and (1-OR) was used to assessthe efficacy of BCG to prevent tuberculous meningitis.Results Four out of sixteen tuberculous meningitis patients werevaccinated, while 10 of 16 primary tuberculosis patients were vac-cinated (p=0.03). OR of vaccinated patients to get tuberculousmeningitis was 0.2 (95%CI 0.04;0.91). The efficacy of BCG vacci-nation to prevent tuberculous meningitis was 1-0.2 = 0.8. The riskof severe malnourished patients to get tuberculous meningitis was2.33 (95%CI 0.52;10.48; p=0.26).Conclusion Most tuberculous meningitis patients were not BCGvaccinated. Severe malnutrition did not play role in the occurrenceof this disease